PENGARUH KEADILAN ORGANISASI, KEPEMIMPINAN TRANSFORMASIONAL DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA KARYAWAN DEALER HONDA KECAK MOTOR DALUNG - Putu Gde Cahya Krisnanda; Pande Ketut Ribek; Tiksnayana Vipraprastha (VALUES, 2024)
Human resources are really needed by companies as system managers and subjects of implementing company policies and operational activities to achieve predetermined goals. If human resources are managed well, they can support the business success of a company. In a company, human resources are very necessary to act as drivers for the various kinds of work that will be carried out by employees. This research aims to examine and analyze the influence of organizational justice, transformational leadership and work motivation on employee job satisfaction. This research was conducted at the Honda Kecak Motor Dalung Dealer located on Jl. Raya Padang Luwih, No. 166, Badung Regency, Bali, 80361, with operational areas in Bali. The population in this study were 37 employees at the Honda Kecak Motor Dalung Delaer using the questionnaire method. Data collection techniques include observation, interviews, documentation and questionnaires. Data analysis techniques used. The types of data used in this research are quantitative data and qualitative data. The data sources used in this research can be classified into two, namely primary data and secondary data. All data obtained from the questionnaire distribution is suitable for use, then analyzed using multiple linear regression, hypothesis testing (t test and f test). The research results show that (1) Organizational justice has a positive and significant effect on employee job satisfaction at the Honda Kecak Motor Dalung Dealer. (2) Transformational leadership has a positive and significant effect on employee job satisfaction at the Honda Kecak Motor Dalung Dealer. (3) Work motivation has a positive and significant effect on employee job satisfaction at the Honda Kecak Motor Dalung Dealer.